Pengaruh Green Accounting, Shared Public Capital dan Firm Size Terhadap Profitabilitas Perusahaan: (Studi Kasus Pada Perusahaan Basic Material yang Terdaftar di Bursa Efek Indonesia Tahun 2020 - 2022) - Selfiani, Ni Kadek Monica; Kusumawati, Ni Putu Ayu; Yuliantari, Ni Putu Yeni (Hita Akuntansi dan Keuangan, 2025)
One way to evaluate a business is by looking at its profitability ratio. Achieving maximum profit or profit while simultaneously improving the well-being of all stakeholders—the corporation, society, and the environment—is not an option. The purpose of this study is to analyse basic materials firms listed on the Indonesia Stock Exchange in 2020 and 2022 to find out how company size, green accounting, and public shared capital affect profitability. A total of 207 firms trading on the Indonesia Stock Exchange make up the study's population. Multiple Regression Analysis is the method used for data analysis. The research findings reveal that among basic material companies listed on the Stock Exchange in 2020–2022, the variables of Firm Size and Green Accounting significantly impact profitability, whereas the variable of Public Shared Capital does not. This study aims to provide future researchers with the necessary information to further investigate the relationship between Green Acconting, Public Shared Capital, and Firm Size as indicators of profitability.